Word-entries and Big Data in Lexicons of Early Modern English - Lancashire, Ian (Renaissance and Reformation / Renaissance et Réforme, 2014)
This brief thirty-year history of Lexicons of Early Modern English, an online database of glossaries and dictionaries of the period, begins in a fourteenth-floor Robarts Library lab of the Centre for Computing and the Humanities at the University of Toronto in 1986. It was first published freely online in 1996 as the Early Modern English Dictionaries Database. Ten years later, in a seventh-floor lab also in the Robarts Library, it came out as LEME, thanks to support from TAPoR (Text Analysis Portal for Research) and the University of Toronto Press and Library. No other modern language has such a resource. The most important reason for the emergence, survival, and growth of LEME is that its contemporary lexicographers understood their language differently from how we, our many advantages notwithstanding, have conceived it over the past two centuries.